The influence of floaters on players` tactical behaviour in small-sided and conditioned soccer games - Bach Padilha, M.; Guilherme, J.; Serra-Olivares, J.; Roca, A.; Teoldo, I. (International Journal of Performance Analysis in Sport, 2017)
This study examined players` tactical behaviours based on core tactical principles during small-sided and conditioned games (SSCG) with and without floaters on the sidelines. A total of 24,068 tactical actions performed by 168 Under-17 academy soccer players were assessed using the System of Tactical Assessment in Soccer (FUTSAT) across two different SSCG: "Floaters off" (Gk+3 vs. 3+Gk) and "Floaters sidelines" (Gk+3 vs. 3+Gk+2 floaters). Results revealed that players showed different tactical behaviours depending on the SSCG format and playing phase. In "Floaters off" SSCG, players more frequently performed the core tactical principles of concentration during the defensive phase and penetration for the offensive phase of play creating more opportunities for 1 vs. 1 situation. In contrast, in the "Floaters sidelines" SSCG, players made more effective use of playing space (width and length) in the opponent`s half during the offensive phase and limited the space for the opponent by compacting the defence in their own half (defensive unity) due to numerical disadvantage during defensive phase. Findings suggest that the use of floaters (on the sidelines) encourage players to keep ball possession during offensive organisation, as well as promote the team`s defensive stability by decreasing the spaces between teammates during defensive organisation.